Analisis Pengelolaan Keuangan Desa Tahun 2020 di Nagari Pakan Rabaa Timur Kecamatan Koto Parik Gadang Diateh Kabupaten Solok Selatan - Indra Pebi Susanto; Netra Surianto; Riza Eka Putri; Zulsantoni Zulsantoni (CV. Strata Persada Academia, 2023)
This study chose Nagari Pakan Rabaa Timur because it is the best Nagari in terms of budget discipline and improvements towards the future, the purpose of this research is to find out and analyze the suitability of village financial management in 2020 in Nagari Pakan Rabaa Timur with village financial management according to Permendagri No. 20 of 2018. The research method used in this research is descriptive qualitative research. This descriptive approach is used in order to obtain descriptive data in the form of written words from people or samples used as research respondents, qualitative research is used to examine natural object conditions. From the analysis conducted by researchers between practices in Nagari Pakan Rabaa Timur and Permendagri No. 20 of 2018, the 2020 village financial management stage in Nagari Pakan Rabaa Timur has been carried out according to Permendagri No. 20 of 2018 concerning the management of village finances, but all of this still depends on the guidance and instructions of the nagari guardian.